MANAJEMEN PEMBELAJARAN KETERAMPILAN BERBAHASA ARAB DENGAN METODE ROLE PLAYING BAGI SANTRI KELAS IV KMI PONDOK PESANTREN AL IMAN WONOGIRI - Buchari, Buchari (El-Hayah, 2018)
Abstract : Research background reveals about speaking Arabic is important and must be mastered fluently by all students in Islamic Boarding School. This research aims at determining: 1) the planning of learning Arabic using role playing method at Islamic Boarding School Al Imam Wonogiri; 2) the implementation of learning  Arabic using role playing method at Islamic Boarding School Al Imam Wonogiri; 3) the evaluation of learning Arabic using role playing method at Islamic Boarding School Al Imam Wonogiri; 4) the development of learning Arabic using role playing method at Islamic Boarding School Al Imam Wonogiri.This research was descriptive qualitative. It was conducted at Islamic Boarding School of Al Iman Wonogiri. Informants of this research were Arabic teachers of Islamic Boarding School of Al Iman Wonogiri, especially 4th grades KMI and the Principal. Technique of collecting data used interview, observation, and documentation. Technique of data validity applied triangulation of source and method. Technique of data analysis used interactive model, including data collection, data reduction, data display and conclusion. The results of this research show that: 1) the planning of learning Arabic is done by summarizing purpose and objective of learning, choosing and determining learning subject, and also determining learning source or learning media; 2) the implementation of learning Arabic using Role Playing covering: the teachers create a group to practice role playing, explain learning theme to play role, give chances for students to discuss, monitor the students playing role, appreciate and evaluate learning activities. However, the teachers must be competent in their field; 3) the evaluation of learning Arabic using Role Playing is based on the following criteria: ability in speaking, writing, and mastering language formula, vocabulary, grammar, dialect, fluent speaking, carefulness in speaking and writing. The students should join test, assignment, housework or practice.       Keywords: Arabic learning, and Islamic Boarding School Al Iman Wonogiri